Cultural Orientation, Cross-Cultural Communication, and Responsive Pedagogy: Considerations for Inclusive Classrooms in Adult Education - China Carter-Jenkins; Mary Alfred (Adult Education Research Conference, 2010)
In this paper, we explore the relationship between cultural orientation, cross-cultural communication and culturally-responsive pedagogy in university classrooms. Due to the rise of foreign-born learners and citizens of color in higher education institutions, educators should consider the dynamics of individualist and collectivist orientations and how they influence classroom communication. Drawing from the literature and our own practice, we explore ways to make the classroom more welcoming for students of nonwestern social and educational traditions.